Method and Circuit for the Multi-Phase Operation of an Electric Motor - Austermann, Johann; Borcherding, Holger
The invention relates to a method for operating an electric motor in a generator mode, said electric motor being connected to at least three phases of a power supply network. An energy that is to be fed back into the power supply network (L1, L2, L3) is connected from a DC voltage intermediate circuit (3) of a frequency Converter (1) to the network phase of the highest voltage as an intermittent and averaged power block by a synchronous inverter (10). A circuit is used in which a DC-DC Converter (9) is fed from a DC voltage intermediate circuit (3) of the frequency Converter (1), wherein a synchronous inverter (10) is connected downstream of the DC-DC Converter and a network filter (11) is connected downstream of the synchronous inverter (10).